First report of Agaricus sect. Brunneopicti from Pakistan with descriptions of two new species - Bashir, Hira; Hussain, Shah; Khalid, Abdul Nasir; Niazi, Abdul Rehman Khan; Parra, Luis A.; Callac, Philippe (Phytotaxa, 2018)
Agaricus is a genus of saprophytic fungi in the Basidiomycota. As part of ongoing studies on the genus Agaricus in Pakistan, we here describe and discuss two new species, A. pakistanicus sp. nov. and A. sparsisquamosus sp. nov. Morphological characters and phylogenetic analysis of ITS sequences were used to clarify their taxonomic affinities. Phylogenetic analysis indicated that both species belong to A. sect. Brunneopicti. This palaeotropical section, which has been recently reconstructed, is reported in Pakistan for the first time. Interestingly, these two new species exhibit a reddish or brown discoloration. With these two new species, the distribution of this section, which was previously restricted to tropical and subtropical humid regions, now extends to semi-arid and desert climate regions and the total number of species in the section increases to 20, including eight unnamed species.